Development of pea protein-derived 3D foam scaffolds cross-linked with heat and tannic acid for cellular agriculture applications - Woo-Ju Kim; Yoonbin Kim; Begum Koysuren; Nitin Nitin (Current Research in Food Science, 2025)
Plant protein-based, 3D-structured scaffolds that mimic the mechanical properties of conventional meat products while supporting cytocompatibility and cellular growth are essential for developing alternative meat products. This study evaluates the development of pea protein isolate (PPI)-derived 3D foam scaffolds for cellular agriculture using heat and tannic acid (TA) as cross-linking agents. Infrared (IR) spectroscopy and scanning electron microscopy (SEM) analyses demonstrated the effects of thermal and TA treatments on the cross-linking of the proteins and microstructure of the PPI foam scaffold. Textural profile analysis (TPA) revealed that the mechanical properties of the fabricated scaffolds are comparable to those of conventional meats and meat analogues, and the addition of TA increased the hardness and reduced the cohesion of the scaffold. The result of the in vitro digestibility test demonstrated that the scaffolds exhibited a free amino acid release profile similar to that of pea protein gels. The cytocompatibility of the 3D foam scaffolds was evaluated using C2C12 myoblast cells as a model cell line. Rapid adhesion and significant proliferation of the cells were observed on the 3D foam scaffolds. Overall, the findings of this study highlight the potential of plant-based, 3D foam scaffolds for cellular agriculture applications.